Triaxial Magnetic Flux Emanation in Response to Uniaxial Electric Field in Magnetoelectric Composite Cylinder Structure. Issue 15 (11th June 2020) - Youssef, George; Newacheck, Scott; Lopez, Mario; Stampfli, Ryan
Abstract : Magnetoelectricity in bulk strain‐mediated multiferroic composites has been growing in attention for sensor and actuator applications. For actuator applications, where electric to magnetic coupling is utilized, the magnetoelectric composite alters the magnetic field which it is within resulting in full‐field spatial and directional changes to the magnetic flux. To grasp a better understanding of the full‐field magnetic behavior of a magnetoelectric composite with a complex geometry, multiple magnetic flux measurements in different locations and directions are taken to unveil interesting behaviors and phenomena such as modality and postfabrication material property modification. Remarkably, a significant multidirectional magnetic flux is measured at a distance away from the composite which can be harnessed to improve the efficiency of multiferroic actuators. In addition, the intensity and directionality of the magnetic flux is highly tunable by modifying the frequency and bias magnetic field depending on the need for the application. Abstract : Localized and remote measurements of orthogonal magnetoelectric measurements reveal tunability through manipulation of materials properties. The intensity and directionality of the coupling coefficient can be frequency and magnetic bias modulated to suit the application. The local multidirectional magnetoelectric behavior can be harnessed to improve the efficiency of multiferroic actuators, whereas the remote response can be exploited in energy transfer.